Prioritized Attributes on Black Rice Product Development: Kano Model Application - Shafira Wuryandani (APTA and DTIP FTP UGM, 2021)
Black rice is a functional food that contributes to its increasing of popular for consumption and the increasing consumer awareness of health. However, the quality of black rice products still needs to be improved to meet consumer needs. This research was conducted to determine how black rice consumers voice the attributes of black rice products circulating in the market and what priorities need to be made to develop black rice products. The research data was collected through a survey of 50 black rice consumers. The survey was conducted using a questionnaire prepared according to the Kano Model. Data analysis was carried out using the Kano Model, which was developed with the preparation of the House of Quality to determine the priorities that need to be carried out in developing black rice. The results show that the attributes of black rice are divided into two categories: attractive and indifferent. Attributes included in the attractive category are organic black rice, vacuum packaging, nutritional values , and cooking methods on the packaging. Other attributes fall into the indifferent category. Product development priorities focus on attributes that are in the attractive category. The priority for developing black rice products is planting with organic and certified methods, vacuum packaging, new packaging designs that include nutritional values , and cooking methods.